Body composition in children with renal disease: use of dual energy X-ray absorptiometry - Cochat, P; Braillon, P; Feber, Janusz; Hadj-Aissa, A; Dubourg, L; Liponski, I; Said, M. H; Glastre, C; Meunier, P. J; David, L (Pediatric nephrology, 1996)
Dual energy X-ray absorptiometry (DEXA) is a non-invasive accurate method which estimates bone mineral content and density (BMD), as well as fat (FM) and lean (LM) body mass. This method was used in control children in order to establish normal values for BMD of lumbar spine and whole body composition ?logistic curves, general equation E = k+K/[1+ alpha exp(- beta A)]?. In children with chronic renal failure (CRF), LM correlated with the urinary excretion of creatinine (r = 0.97, P = 0.0001) independently from glomerular filtration rate. However, the assessment of LM by DEXA must take into account the hydration level, since there is a positive correlation between fluid loss and reduction in LM in children on hemodialysis (r = 0.98, P = 0.0001). After renal transplantation, a significant loss of BMD (median -9.2%) was observed at 6 months which returned to 95% of pretransplant values by the end of the 1st year. Maximal changes in LM and FM occurred during the first 3 months (-7.8% and +7.2%, respectively) and may be due to steroids; these should be influenced by physical activity since FM correlated inversely with maximal oxygen consumption (r = 0.69, P = 0.0001). Recombinant growth hormone treatment could also increase LM and decrease FM, as shown in 9 patients. DEXA appears therefore to be a reliable method for evaluating therapeutic interventions affecting nutritional status in children with CRF.
Keywords: Infant; dospělí; hodnoty glomerulární filtrace; růstový hormon; Kidney Transplantation; předškolní dítě; Humans; páteř; transplantace ledvin; Absorptiometry, Photon; spotřeba kyslíku; složení těla; absorpční fotometrie; mužské pohlaví; Kidney Failure, Chronic; Child, Preschool; Adult; Adolescent; Body Composition; Spine; kostní denzita; dialýza ledvin; Oxygen Consumption; Growth Hormone; ženské pohlaví; Renal Dialysis; lidé; mladiství; dítě; chronické selhání ledvin; Child; Glomerular Filtration Rate; Bone Density; Male; kojenec; Female